Drop coating deposition Raman (DCDR) spectroscopy of contaminants - Kuižová, Alžbeta; Přikryl, Mikuláš; Procházka, Marek; Kočišová, Eva (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2021)
Raman spectroscopy is a useful technique to identify small organic molecules, including contaminants. The drop coating deposition Raman (DCDR) is more sensitive than conventional Raman spectroscopy from solution. It is based on Raman measurement from a small drop dried on a hydrophobic surface where studied molecules are preconcentrated. In this paper, DCDR spectra of dried drops of selected contaminants (food contaminant melamine, fungicide thiram, herbicides bentazon and picloram) on the hydrophobic substrate were acquired for the first time, whereas Raman spectra from stock solutions were impossible to obtain under the same experimental conditions. The lowest DCDR detected concentrations were determined as 6.4 µM, 0.31 µM, 20 µM and 2 µM in deposited concentrations for melamine, thiram, bentazon and picloram, respectively. Therefore, DCDR spectroscopy can serve to detect these molecules in concentrations relevant in food/groundwater contaminations.
Keywords: Hydrophobic and Hydrophilic Interactions; Spectrum Analysis, Raman; Ramanova spektroskopie; DCDR; Contaminant; Thiram; Drop coating deposition Raman; Bentazon; Melamine; Picloram; hydrofobní a hydrofilní interakce